Both follow the normal proof methods ....

Note that P(X,Y|e) = P(X,Y,e)/P(e)

and P(X|Y,e) = P(X,Y,e)/P(Y,e)

and P(Y|e) = P(Y,e)/P(e)

The first part is immediate from this.

The second part is almost trivial after this ...

Note that,

P(X,Y|e) = P(X|Y,e) P(Y|e)

also,

P(X,Y|e) = P(Y|X,e) P(X|e)

Can u finish it off from here?

-- AI

--- In

aima-talk@yahoogroups.com, "brandon_pitt_47"

<brandon_pitt_47@y...> wrote:

>

>

> Hope someone can help me with this one. completely stuck. any

solutions out there? it's

> on page 490 about proving the conditionalized version of the general

product rule.

>

> P(X,Y|e) = P(X|Y,e) P(Y|e)

>

> part b: prove the conditionalized version of Bayes' Rule in

Equation (13.10)

>

> P(Y|X,e) = P(X|Y,e) P(Y|e)

> ------------

> P(X)

>

> ANY HELP WOULD BE GREAT.

>

> thanks,

> brandon